2015
DOI: 10.1159/000371524
|View full text |Cite
|
Sign up to set email alerts
|

Pili Annulati and Trichorrhexis Nodosa in the Same Patient: Cause or Coincidence?

Abstract: Purpose: To determine the relationship between pili annulati (PA) and acquired trichorrhexis nodosa (TN) seen in the same patient, considering the two main theories evoked by previous studies: greater stiffness of darker PA bands or associated cuticular damage. Procedures: Light microscopy of hair shafts from different regions of the patient's scalp. Results: TN was not superimposed to dark bands of PA. Conclusions: Greater stiffness of darker PA bands was excluded as the cause of hair breakage. Hair breakage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…So far, there have been case reports of trichorrhexis nodosa with pili annulati [7,8]. To the best of our knowledge, ours is the first case of pili torti, pili annulati, and trichorrhexis nodosa in the same individual with autosomal dominant inheritance.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…So far, there have been case reports of trichorrhexis nodosa with pili annulati [7,8]. To the best of our knowledge, ours is the first case of pili torti, pili annulati, and trichorrhexis nodosa in the same individual with autosomal dominant inheritance.…”
Section: Discussionmentioning
confidence: 65%
“…Pili annulati may be seen sporadically or inherited as an autosomal dominant trait. Although pili annulati has been classified as a hair shaft defect without fragility, fragility may be found due to associated trichorrhexis nodosa [7,8]. Trichorrhexis nodosa is the most common among all hair shaft defects and is characterized by hair shaft fracture due to damage to the cuticle and intercellular cement responsible for binding cells together [4].…”
Section: Discussionmentioning
confidence: 99%
“…An alternate hypothesis to explain the breakage seen in PA stems from the difference in stiffness noted between the light and dark bands when using atomic force microscopy to study the mechanical properties of PA hair shafts [9]. However, in the report of a patient with PA and acquired TN, the use of light microscopy demonstrated that TN occurred in some hairs unaffected by PA and in sites other than the dark PA bands, which favors cuticular damage rather than band stiffness as a predisposing factor to weathering [10]. The increased fragility observed could also partly result from a reduced cysteine content in PA hair, since amino acid analyses have demonstrated that PA hairs have a significantly lower cysteine content and a higher lysine content when compared to normal hairs [7].…”
Section: Discussionmentioning
confidence: 99%
“…One case describes a 39-year-old female with PA, trichostasis spinulosa, and episodic TN that occurred after illness or pregnancy [11]. The other three cases describe adult patients who have overused heating tools or have had harsh hair styling practices [8,10,12]. These cases suggest that vigorous mechanical or chemical trauma of a PA hair shaft predisposed to weathering could lead to TN or TN-like changes.…”
Section: Discussionmentioning
confidence: 99%
“…It is traditionally considered as a hair condition without associated fragility but there are reports of pili annulati that show hair fragility (Donati et al 2015). • Clinical feature: In this condition, alternating light and dark bands are seen along hair shafts, leading to a speckled-appearing scalp hair (Singh and Miteva 2016).…”
Section: Trichothiodystrophymentioning
confidence: 99%